TECHNIQUE OF QUESTIONING CARRIED OUT BY NOVICE TEACHERS - Sri Wayuni, Sri Wahyuni (ETERNAL, 2010)
Abstract: When teachers conduct a lesson, the activity of posing questions always appears in it. The activity of posing questions includes the skills of basic questioning and advanced questioning in which a teacher must acquire. The focus of the study is on the basic questioning techniques only. Â The purposes of this study are aimed at finding: 1) the basic questioning component skill used by the novice teachers in the classroom, 2) the types of question used by the novice teachers in the classroom, and 3) the levels of questioning category used by the novice teachers in the classroom. This discourse study was based on the analysis of the teacher talk in class. The analysis was based on the recorded data of the five novices when they conducted lessons in class. The recorded data were transcribed. From the transcriptions, teachersâ talk were identified and classified into types of questions, levels of questions, and basic questioning components. The findings of the study are: 1) novices used higher number of closed questions; 2) there were more low level questions conducted by novices; 3) the large number of the skill components in their teaching activities were the distributing, pausing and reacting. Â Key Words: Novice Teachers, Technique of Questioning,